The histories of the Latin American church : a brief introduction - Cruz, Joel Morales (Fortress Press, 2014)
The story of Latin American Christianity is too often appended to the end of larger narratives and is rarely given the full consideration it deserves. And yet, the rich stories of Christianity in Latin America deserve our full attention. With this brief, engaging, and helpful overview, Joel M. Cruz offers a resource that tells that story in a new way, enabling students of all kinds to better understand the histories of Latin American Christianity. Cruz's text is divided into two parts. The first explores the history of the region in all of its diversity and variation. The second explores the theology of Latin America by way of three essential issues faced by the encounter of European Christianity with native peoples and African slaves: anthropology, ecclesiology, and soteriology. The result is an informative and eye-opening introduction to a kaleidoscope of efforts to articulate the meanings and implications of Christianity in the context of Latin America.